Productivity of Maize Genotypes under Different Planting Dates - Bahadur, B.K. Santa; Karki, Tika Bahadur; Shrestha, Jiban; Adhikari, Parbati (Our Nature, 2015)
Genotypic yield potential of maize genotypes is greatly affected by planting dates. This study was conducted to determine optimum planting dates of maize genotypes in 2013/14 at Rampur, Chitwan, Nepal. Four genotypes namely RML-4/RML-17, RML-32/RML-17, ACROSS-9944/ACROSS-9942 and S99TLYQ-B were planted at every week from April to March. The experiments were laid out in randomized complete block design with four replications . The result of experiment showed that the highest production (5565 kg/ha) was obtained in August followed by February (5266 kg/ha), June (4475 kg/ha) and July (4255 kg/ha) respectively. The lowest yield (2572 kg/ha) was obtained in the month of November and December planting (3019 kg/ha). The highest grain yield was obtained in RML-4/RML-17 (7392 kg/ha) and RML-32/RML17 (6606 kg/ha), ACROSS- 9944/ACROSS-9942 (5004 kg/ha) during August planting and higher yield of QPM variety S99TLYQ-B was obtained in the month February planting. Winter maize has higher production potential than the rainy season maize. Based on this experiment RML-4/RML-17, RML-32/RML17 and ACROSS- 9944/ACROSS-9942 should be planting in August (winter season) and S99TLYQ-B in February (spring season) for higher grain yield production. Our Nature (2015), 13(1): 45-49